Policy perspectives in Indian economic development ; essays in honour of Prof. G.S. Bhalla - Chadha, G.K.(ed) (New Delhi, 1994)
In recent years, new development directions are taking roots in the Indian economy, partly in response to compul sions internally accummulated over years, and partly to adjust to the chang ing economic circumstances outside India. In this transitional phase, the positive and negative features of India's past development experience must be thrown bare so that the nuanc es of change are grasped with clarity and objectivity. This book, brought out in honour of Prof. G.S. Bhalla does precisely the same. It is based on a set of edited papers, written expressly for the volume by a team of renowned schol ars. The strong team of paper writers has ensured a high degree of academic depth and empirical rigour, analytical objectivity free of ideological predilic tions, a rich diversity of topics covered and cross-section of valuable opinions, and so on. All this makes the volume highly useful to policy administrators at all levels of national life, to individ ual institutions, scholars and public men concerned with India's development efforts.
Keywords: India- Economic development- 1993